ABNORMALITIES OF INTER-SYSTEMIC INTERACTIONS IN CHRONIC INFLAMMATORY PROCESS - E. P. Kalinina (SPb RAACI, 2014)
Abstract. A purpose of present work was to detect some abnormal inter-systemic interactions in chronic disease. Forty-eight patients with chronic obstructive pulmonary disease were under examinations. They belonged to middle-aged group (58±4 years old), with mean disease duration of 11,2±5,2 years. Analysis of laboratory parameters has revealed certain influence of immunocompetent cells, intercellular regulation factors, and some parameters characterizing the state of biomembranes, upon clinical course of chronic inflammatory disorder. The method of «correlation pleyades» enables detection and objective estimation of interrelations between all the quantitative indicators of resistance that may determine clinical prognosis, outcomes of chronic disease, and efficiency of therapy applied.